St. Louis's "urban prairie": Vacant land and the potential for revitalization. - Prener, Christopher G.; Braswell, Taylor Harris; Monti, Daniel J. (Journal of Urban Affairs, 2020)
As part of a larger project to understand the relative health and disorder of St. Louis's neighborhoods, this article presents estimates of the number of vacant parcels in the city. These estimates, which are considerably higher than previously published ones, are heavily concentrated in the city's disinvested and segregated north side. We term this heavy concentration of vacancy urban prairie. After accounting for other factors as well as possible sources of statistical error, we identify both long-term population loss since 1970 and the proportion of African American residents as significant covariates associated with the amount of urban prairie land per neighborhood. These high levels of concentrated vacancy lead us to critique the city's existing approaches as being too limited in scope and to suggest a range of possibilities for revitalizing portions of northern St. Louis while allowing prairie land to continue to exist in others.